Post Covid-19 Syndromes, The Time line of Covid - Shams, Nadia; Umar, Zaid; Meraj, Lubna; Ayub, Neelam; Waseem, Muhammad; Virk, Kazim Abbas (Journal of Rawalpindi Medical College, 2023)
BACKGROUND & OBJECTIVES: Novel corona virus has claimed significant mortality and morbidity. Timeline of long-term complications and effects on humanity are yet to be explored. Current study aims to evaluate the spectrum of post Covid syndromes in our Covid survivors. METHODOLOGY: This observational study was conducted at Medicine Dept. RIHS Islamabad after ethical approval. 195 recovered COVID cases were selected and followed 3 monthly over a year. Inclusion criteria: Age >12 years, both genders, Covid PCR+ve >4 weeks earlier. Exclusion criteria: Malignancies, pregnancy, recurrent Covid and that lost follow-up. Patients were evaluated for new onset generalized symptoms, respiratory, cardiovascular, neurological, hematological, gastrointestinal, dermatological and genitourinary supported by relevant investigations. Data analyzed by SPSS-22 with significant p<0.05. RESULTS: Amongst 195 cases, 102(52.3%) males and 93(47.7%) females, mean age was 42.35+14.31 years, mean duration since Covid recovery 32+24.47 weeks. There was history of mild COVID in 89(45.6%), moderate 71(36.4%), severe 32(16.4%) and life threatening 02(01%) having significant association with increased mean age and female gender (p<0.05). ninety four (48.2%) cases had post COVID syndromes. persistent fatigue (58), fever (29), myalgia’s (27), dyspnea (26), persistent cough (19), weight loss/gain (18), smear positive TB (2), bronchitis (7), asthma exacerbations (3) and pleural effusion (1). X-ray findings showed lung fibrosis in 12, ground glass appearance 10. Spirometry showed reduced exercise capacity in 11. Anemia in 11, leukopenia 02, thrombocytopenia 02, pancytopenia 01 case. In CVS, retrosternal chest pain in 11, orthopnea/PND 05, myocarditis/myocardial fibrosis 04, pericardial effusion 01, new onset hypertension 03, worsened hypertensive control 02, palpitations 10 and POTS 03. Regarding ENT, sinusitis in 12 and mucor-mycosis 03. Reduced GFR 05 and COVAN 01. New onset diabetes 05, worsened diabetic control 06, bone-demineralization 03 and thyroiditis 01. Persistent diarrhea 06, IBS 04, gastritis 08, esophagitis 06, GERD 11. Seven of 93 females reported menstrual irregularities. Hair loss 15, rash 07. headache in 23, anxiety 17, disturbed sleep 14, depression 09, peripheral neuropathy 03, CVA 03, amnesia and PTSD 03 each. 03 cases expired with cardiopulmonary arrest. CONCLUSION: Post COVID syndrome observed in half of Covid survivors. The respiratory, cardiovascular, dermatological, neuropsychiatric and generalized symptoms were frequent. Authors suggest follow-up of Covid survivors. The clinical evaluation and timely management may improve quality of life and morbidity amongst survivors. KEY WORDS: COVID-19. Post Covid Syndromes. Long Covid syndrome. Covid complications. Persistent post-Covid syndrome (PPCS), Myocarditis. Lung Fibrosis.